Becoming a better value creator : how to improve the company's bottom line--and your own - Thakor, Anjan V. (University of Michigan Business School management series., 2000)
"Today's companies don't need better managers. They need better value creators - individuals who understand not only the organizational process but the organizational dynamics that ensure continuing profits for a company and its shareholders. In this book, Anjan Thakor presents managers with a pragmatic guide to creating value and boosting the success of their companies - while enhancing their own careers."